IMPROVING LITERACY OF CLEAN AND HEALTHY LIVING BEHAVIOUR FOR ENVIRONMENT-BASED DISEASE PREVENTION IN WETLAND COMMUNITIES: PENINGKATAN LITERASI PERILAKU HIDUP BERSIH DAN SEHAT UNTUK PENCEGAHAN PENYAKIT BERBASIS LINGKUNGAN DI KOMUNITAS LAHAN BASAH - Wahyu Setyaningsih; Nika Sterina Skripsiana; Muhammad Alrizal Rahman; Nursyfa Nursyfa; Thabita Aliya Hasana; Najma Aliya; M. Syauqi Fathurrahman; Yehezkiel M. P. Sitompul (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: People living in wetland areas often face many diseases caused by poor sanitation, unhealthy diets, and low physical activity. These problems are connected to low health literacy, which makes it harder for people to find, understand, and implement Clean and Healthy Living Behaviour (CHLB) in their daily routines. Improving health literacy is important for helping people make better choices and support behavior change. Objective: This study aims to improve health literacy related to CHLB as an environmentally based disease prevention strategy in wetland communities. Method: A pre-experimental one-group pretest–post-test design was used to assess 32 participants, including participatory health education through presentations, videos, posters, and leaflets, as well as health check-ups. Knowledge was measured using structured questionnaires, and data were analyzed using the Wilcoxon signed-rank test. Results: The average knowledge score rose from 79.37 to 91.87 (p < 0.001). Most participants had normal blood glucose levels, but hypertension remained common at 65.523%. Conclusion: The intervention improved health literacy about CHLB and supports its use as a primary strategy to prevent environmentally related diseases in wetland communities.